Pelatihan Optimalisasi Facebook Marketing dan Konten Strategi Foto Produk pada UMKM Kampung ATBM Desa Cepagan - Ari Muhardono; Danang Satrio; Heni Indah Lestari; Ahmad Adi Fadhilah (Edumedia Solution, 2022)
2020 is a year full of challenges that will change the dynamics of the global economy. The Covid-19 pandemic has forced governments around the world to take drastic measures to stop the spread of the virus in all activities including economic activity. The people's weaving industry (ATBM) in Cepagan Village, Warungasem District, Batang Regency is a potential industry and is a center for the creative industry of Non-Machine Weaving Equipment (ATBM). But unfortunately, the Covid-19 pandemic has forced most weaving craftsmen to lose market share. In fact, they are forced to go out of business and sell some weaving equipment to meet their daily needs. The traditional woven fabric market is average in tourist cities, such as in Bali, Lombok, as well as several European countries. But because of the pandemic, the turnover fell drastically to 90% because all access was closed and there was no demand, so it was very difficult to market it. One of the most solutive ways in marketing activities during the pandemic is online marketing using social media. The MSMEs in Cepagan Village as processors of woven clothing of the ATBM type have used Facebook social media in their online marketing activities, but knowledge related to the use of Facebook for online marketing media purposes still minimal. For this reason, the Community Service Proposing Team is interested in holding Facebook Marketing Optimization training activities for MSME Personal Branding and Sales Increase